Prosocial Behavior Mitigates the Negative Effects of Stress in Everyday Life. (July 2016) - Raposa, Elizabeth B.; Laws, Holly B.; Ansell, Emily B.
Recent theories of stress reactivity posit that, when stressed, individuals tend to seek out opportunities to affiliate with and nurture others to prevent or mitigate the negative effects of stress. However, few studies have tested empirically the role of prosocial behavior in reducing negative emotional responses to stress. The current analyses used daily diary data to investigate whether engaging in prosocial behavior buffered the negative effects of naturally occurring stressors on emotional well-being. Results showed that on a given day, prosocial behavior moderated the effects of stress on positive affect, negative affect, and overall mental health. Findings suggest that affiliative behavior may be an important component of coping with stress and indicate that engaging in prosocial behavior might be an effective strategy for reducing the impact of stress on emotional functioning.